The health and safety impact of construction project features. Issue 1 (14th January 2014) - Manu, Patrick; Ankrah, Nii; Proverbs, David; Suresh, Subashini
Abstract : Purpose: – Despite the established significance of underlying accident causes to health and safety (H&S), and the persistent reporting of the underlying accident causal influence of construction project features (CPFs) which emanate from pre-construction decisions, no empirical research has focused on CPFs in terms of assessing their degree of potential to influence accident occurrence. The purpose of this paper is to, therefore, investigate this facet of the accident causal influence of CPFs. Design/methodology/approach: – A mixed method design was used involving semi-structured interviews, and a questionnaire survey of UK construction professionals. Findings: – CPFs generally have a moderate or a high potential to influence accident occurrence, implying a fair or severe potential to cause harm in terms of the H&S of workers. The degree of potential of CPFs to influence accident occurrence is influenced by: the extent to which certain proximate causes of accidents are common/prevalent within CPFs;and the degree of potential of those proximate causes to influence accident occurrence. Originality/value: – These findings provide insight into the H&S consequences of CPFs, awareness of which is essential if pre-construction project participants are to implement appropriate risk control measures especially in the early phases of projects to mitigate the accident causal influence of CPFs. The findings reinforce the contribution of clients and their design and project management teams to accident causation, the significance of the early planning of H&S in construction project delivery, and the importance of driving mechanisms such as the Construction (Design and Management) Regulations 2007.